ANALISIS UNSUR KONDISI FISIK DOMINAN ATLIT BULUTANGKIS PB. SATRIA DOMPU TAHUN 2021 - Dita, Ari Ulya; Isyani, Isyani; Taufik, Kurnia (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2022)
Based on the results of observations and interviews, that the coach does not have data about the state or status of the physical condition of the players. As we all know, coaches need to know this by measuring the physical condition of their players so that coaches can provide and determine the intensity of training systematically. The aim of this study was to determine the physical condition of PB badminton athletes. Satria Dompu in 2021. This research is a type of quantitative research with a descriptive survey research method. The research sample used purposive sampling technique, amounting to 15 people. While the data collection technique was carried out using a test instrument for elements of the dominant physical condition including: abdominal muscle strength, endurance, arm muscle strength, speed, agility, and heart endurance. The results of the study can be concluded: (1) The percentage of the athlete’s abdominal muscle strength category is as follows; 1 athlete (6.67%) in very good category, 4 athletes (26.67%) in good category, 8 athletes (53.33%) in moderate category, 2 athletes (13.33%) in poor category. (2) The percentage of the athlete’s arm muscle strength endurance category is as follows; 1 athlete (6.67%) in very good category, 8 athletes (53.33%) in good category, and 6 athletes (40%) in moderate category. (3) The percentage of athlete’s speed category is as follows; 1 athlete (6.67%) in very good category, 2 athletes (13.33%) in good category, 5 athletes (33.33%) in moderate category, 4 athletes (26.67%) in poor category, and 3 athletes (20 %) very low category. (4) The percentage of agility categories of athletes is as follows; 8 athletes (53.33%) in very good category, and 7 athletes (46.67) in good category. (5) The percentage of athlete endurance category is as follows; 2 athletes (13.33%) in the moderate category, 6 athletes (40%) in the poor category, 2 athletes (13.33%) in the poor category, and 5 athletes (33.33%) in the very poor category